Executive Presence for the Academic Chair - Trey Guinn (Academic Chairpersons Conference Proceedings, 2020)
Interactive session emphasizing how communication skills enhance executive presence and shape effectiveness from campus to home. Bring a positive attitude; be ready to learn while having a little fun. Leave with a fresh perspective on how to be a more clear, concise, compelling and confident communicator ready for and more capable of achieving effective executive presence.
Keywords: Communication; Leadership; Management; Confidence; Presentation Skills